1T' RexMo1−xS2–2H MoS2 Lateral Heterojunction for Enhanced Hydrogen Evolution Reaction Performance. (23rd November 2022) - Nguyen, Huong Thi Thanh; Adofo, Laud Anim; Yang, Sang‐Hyeok; Kim, Hyung‐Jin; Choi, Soo Ho; Kirubasankar, Balakrishnan; Cho, Byeong Wook; Ben‐Smith, Andrew; Kang, Joohoon; Kim, Young‐Min; Kim, Soo Min; Han, Young‐Kyu; et al.
Abstract: The imperfect interfaces between 2D transition metal dichalcogenides (TMDs) are suitable for boosting the hydrogen evolution reaction (HER) during water electrolysis. Here, the improved catalytic activity at the spatial heterojunction between 1T' Re x Mo1− x S2 and 2H MoS2 is reported. Atomic‐scale electron microscopy confirms that the heterojunction is constructed by an in‐situ two‐step growth process through chemical vapor deposition. Electrochemical microcell measurements demonstrate that the 1T' Re x Mo1− x S2 –2H MoS2 lateral heterojunction exhibits the best HER catalytic performance among all TMD catalysts with an overpotential of ≈84 mV at 10 mA cm −2 current density and 58 mV dec −1 Tafel slope. Kelvin probe force microscopy shows ≈40 meV as the work function difference between 2H MoS2 and 1T' Re x Mo1− x S2, facilitating the electron transfer from 2H MoS2 to 1T' Re x Mo1− x S2 at the heterojunction. First‐principles calculations reveal that Mo‐rich heterojunctions with high structural stability are formed, and the HER performance is improved with the combination of increased density of states near the Fermi level and optimal Δ G H* as low as 0.07 eV. Those synergetic effects with many electrons and active sites with optimal Δ G H* improve HER performance at the heterojunction. These results provide new insights into understanding the role of the heterojunction for HER. Abstract : The 1T' Re x Mo1− x S2 –2H MoS2 lateral heterostructure is reported to boost hydrogen evolution reaction (HER). At the 1T' Re x Mo1− x S2 –2H MoS2 heterojunction, a Mo‐rich heterojunction with high structural stability is formed, the electron transfer from 2H MoS2 to 1T' Re x Mo1− x S2, and the HER performance is greatly improved with the combination of increased density of states near the Fermi level and optimal Δ G H* of the Mo‐rich heterojunction.